Development of Mobile Location Based Service Application for Searching for Nearest AC Service - Yayat, Asep; Ramadhan, Iksan; Widayanti, Riya; Widiantono, Adi (Journal Sensi: Strategic of Education in Information System, 2025)
Air Conditioner (AC) in the current era has become a necessity in everyday life for use in various activities. Over time, the AC can cause damage generally because it is used frequently, so regular maintenance is needed so that the AC continues to run well and optimally. The problem faced when seeking AC maintenance is difficulty in finding the nearest AC service, so a system is needed that can search according to the customer's location. This search uses a location based service by utilizing the Google Maps API and is mobile based to display location data mapping to see the nearest AC service point. Based on the test results using user acceptance testing, a final score of 93.8% was obtained in the "Very Good" category so that the application runs well and as it should.